PEMBUATAN SOYGHURT SINBIOTIK SEBAGAI MAKANAN FUNGSIONAL DENGAN PENAMBAHAN KULTUR CAMPURAN Streptococus thermophillus, Lactobacillus bulgaricus DAN Lactobacillus acidophilus - Addion Nizori, Viny Suwita, Surhaini, Mursalin, Melisa, Titi Candra Sunarti, dan Endang Warsiki (Jurnal Teknologi Industri Pertanian, 2008)
ABSTRACTThe objective of this research was to study the effect of L. acidophillus concentration on fermented soymilk quality. The experiment used a completely random design with L. acidophillus concentration as a treatment. Three levels of L. acidophillus concentration as probiotic bacteria, i.e.: 1, 2, and 3 % (w/w) were used in this research as addition of yoghurt bacterial culture (S. thermophilus and L. bulgaricus). A control is done for yoghurt without L. acidophilus addition. The result showed that the level of L. acidophillus concentration has a significant effect on pH, lactic acid content and sensory analysis (overall performance acceptability). The best treatment is 3% of L. acidophillus with the product properties of pH 4,45, lactic acid content 0,75%, solid content 11,20% and water content 88,80%.Keywords : probiotics, synbiotics, soymilk and L. Acidophilus